Sperm chromatin-induced ectopic polar body extrusion in mouse eggs after ICSI and delayed egg activation. - Manqi Deng; Rong Li (PLoS ONE, 2009)
Meiotic chromosomes in an oocyte are not only a maternal genome carrier but also provide a positional signal to induce cortical polarization and define asymmetric meiotic division of the oocyte, resulting in polar body extrusion and haploidization of the maternal genome. The meiotic chromosomes play dual function in determination of meiosis: 1) organizing a bipolar spindle formation and 2) inducing cortical polarization and assembly of a distinct cortical cytoskeleton structure in the overlying cortex for polar body extrusion. At fertilization, a sperm brings exogenous paternal chromatin into the egg, which induces ectopic cortical polarization at the sperm entry site and leads to a cone formation, known as fertilization cone. Here we show that the sperm chromatin-induced fertilization cone formation is an abortive polar body extrusion due to lack of spindle induction by the sperm chromatin during fertilization. If experimentally manipulating the fertilization process to allow sperm chromatin to induce both cortical polarization and spindle formation, the fertilization cone can be converted into polar body extrusion. This suggests that sperm chromatin is also able to induce polar body extrusion, like its maternal counterpart. The usually observed cone formation instead of ectopic polar body extrusion induced by sperm chromatin during fertilization is due to special sperm chromatin compaction which restrains it from rapid spindle induction and therefore provides a protective mechanism to prevent a possible paternal genome loss during ectopic polar body extrusion.